Analisis Strategi Orangtua dalam Menanamkan Nilai-Nilai Agama Islam pada Anak di Masyarakat Desa Tapak Gedung Kecamatan Tebat Karai Kabupaten Kepahiang - Roliza Perantika; Nurlaili Nurlaili; Alimni Alimni (UIN Fatmawati Sukarno Bengkulu, 2023)
This research is motivated by observational data which shows the acquisition of results from parents’ strategies in instilling Islamic religious values in children. To respond to this, the researchers conducted a study aimed at finding out the strategies of parents in instilling Islamic values in their children. The objectives to be achieved are to identify, describe, and analyze parents’ strategies for instilling Islamic religious values in children. This research is descriptive qualitative research. This research was conducted on 17 parents in the Tapak Gedung Village community. Research data was obtained from observation, interviews, and documentation. The results of this study are about how parents’ strategies for instilling Islamic values in children. The role of parents in the family is to become educators/teachers at home, parents as facilitators; provide all the needs of children, parents as motivators; give encouragement, support, and encouragement to children, parents as advisers; counselors and supervisors for children and parents as influencers; as a role model and friend who is imitated by children. Islamic religious values are the values of aqidah, morals, and values of worship. Parents’ strategy in instilling Islamic values is essential, considering that parents are the first to introduce Islamic values and educate their children, however, as children mature, higher education is also needed, especially in instilling Islamic values. in children